ANALISA DAN RANCANGAN SISTEM INFORMASI ANTRIAN MENGGUNAKAN BISKITZ CMS - Rizky Tahara Shita; Gandung Triyono (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2011)
Queuing is a less pleasant for many people, especially if the queue is in progress does not irregular. To overcome this things, then it needs a system that helps to be organized and more fun. At some companies, this is already implemented by conducting a computerized queuing system. Thus, the person will get a queue number and wait to be called, to be served by the customer service. Biskitz CMS is a content management system that can be embedded for the purposes of systems that are customizeable and this time biskitz CMS will be implemented to be able to perform the integration with the queue system that will be applied to the Directorate of Finance Bureau of the University of Budi Luhur.Keywords: content management system, queueing systems, biskitz